IMPACT OF DRYING METHODS OVER THE GERMINATIVE POTENTIAL OF CONILON COFFEE OF LATE MATURATION - Posse, Sheila Cristina Prucoli; Rodrigues, Wagner Nunes; Comério, Marcone; Volpi, Paulo Sérgio; Verdin Filho, Abraão Carlos; Posse, Robson Prucoli; Oliveira, Vinicius de Souza; Arantes, Sara Dousseau (Coffee Science - ISSN 1984-3909, 2019)
This study aimed to evaluate the effect of different drying methods (regarding temperature and drying time) over the seed moisture and germination of seeds of Coffea canephora, harvested from genotypes of late maturation. For this end, seeds from selected genotypes were harvested and dried using two different methods: drying at 25 ˚C with natural circulation of air and drying at 35 ˚C with artificial circulation of air. The seeds were evaluated to quantify the loss of moisture content, and their germinative potential was assessed by parameters of germination speed, and the proportion of seedlings with healthy germination originated from them. The results show it is possible to apply different drying methods; using different systems, temperatures and times of exposure; to decrease the moisture content of seeds of C. canephora, from 50% (freshly harvested seeds from genotypes of late maturation, in July) to under 18% (dried seeds). Even if the initial stages of the drying process, while the seeds still present high moisture content, are similar for both methods, the method with artificial circulation of air at 35 ˚C promotes the drying speed and is able to achieve the lower levels of seed moisture using less than half of the time required by method with natural circulation of air at 25 ˚C. This faster moisture removal, however, has negative impacts over the germinative potential of the seeds, which are not observed for seeds subjected to the slow natural drying.